Decision support system for purchasing light fire extinguisher brands (APAR) on household needs using the weighted product (WP) method - Maulana, Dimas Fajar; Heryana, Nono; Ridwan, Taufik (Jurnal Mandiri IT, 2024)
Fire, as a serious disaster with destructive impacts involving loss of material and human lives, is mainly triggered by electrical short circuits due to massive construction and the use of cables that do not comply with standards. The importance of developing electric power that complies with safety standards to protect people and property cannot be overstated. Electrical integration is aimed at increasing system efficiency, but electrical short circuits remain the main cause of fires, accounting for 45% of cases in Indonesia in 2021. To reduce the risk, preventive measures are needed such as repairing the electrical network, using standard equipment, and educating the public. A light fire extinguisher (APAR) is one of the highly recommended fire prevention media. The appropriate APAR for household needs is the Chemical Powder / Dry Cemical type because it is almost effective for all classes of fires, especially for electrical short circuits. But in purchasing we are faced with the many brands available as well as limited needs, desires and financial capabilities. In this context, a web-based Decision Support System (DSS) was developed using the Weighted Product (WP) method to select the Brand of Light Fire Extinguisher (APAR). The WP method gives weight to the criteria of price, quality and reliability, helping households choose an APAR that suits their needs and budget. The application of this method is expected to minimize errors in selecting the APAR brand, increase accuracy, and make it easier to use for those who want to make a purchase. This SPK makes a positive contribution in helping users make APAR purchasing decisions that suit their needs and preferences.